Lattice effects in the quasi-two-dimensional valence-bond-solid Mott insulator EtMe 3 P[Pd(dmit) 2] 2 - Manna, Rudra Sekhar; De Souza, Mariano [UNESP]; Kato, Reizo; Lang, Michael (American Physical Society (APS), 2014)
The organic charge-transfer salt EtMe3P[Pd(dmit)2]2 is a quasi-two-dimensional Mott insulator with localized spins S=1/2 residing on a distorted triangular lattice. Here we report measurements of the uniaxial thermal expansion coefficients αi along the in-plane i=a and c axis as well as along the out-of-plane b axis for temperatures 1.4 K≤T≤200 K. Particular attention is paid to the lattice effects around the phase transition at TVBS=25 K into a low-temperature valence-bond-solid phase and the paramagnetic regime above where effects of short-range antiferromagnetic correlations can be expected. The salient results of our study include (i) the observation of strongly anisotropic lattice distortions accompanying the formation of the valence-bond-solid phase, and (ii) a distinct anomaly in the thermal expansion coefficients in the paramagnetic regime around 40 K. Our results demonstrate that upon cooling through TVBS the in-plane c axis, along which the valence bonds form, contracts while the second in-plane a axis elongates by the same relative amount. Surprisingly, the dominant effect is observed for the out-of-plane b axis which shrinks significantly upon cooling through TVBS. The pronounced anomaly in αi around 40 K is attributed to short-range magnetic correlations. It is argued that the position of this maximum, relative to that in the magnetic susceptibility around 70 K, speaks in favor of a more anisotropic triangular-lattice scenario for this compound than previously thought. © 2014 American Physical Society.
Keywords: 65.40.De; 74.70.Kn; 75.10.Jm; 75.10.Kt